Rehabilitation Strategies and Pain Management in Athletes with Musculoskeletal Injuries - a review - Chowaniec-Rybka, Katarzyna; Bujak, Monika; Sztajura, Jędrzej; Szot, Anna (Journal of Education, Health and Sport, 2026)
INTRODUCTION AND PURPOSE Musculoskeletal injuries, including ligament ruptures, sprains, partial tears, muscle damage, and fractures, are among the most common injuries observed in athletes. Properly conducted rehabilitation is based on early and appropriate patient mobilization following trauma, aiming to restore mobility and strength of the affected musculoskeletal structures during convalescence. Effective management of post-traumatic pain remains a crucial component of therapy, as pain reduction facilitates early mobilization and return to pre-injury functional status. The aim of this study was to review rehabilitation approaches used after various musculoskeletal injuries sustained during sports activity. MATERIALS AND METHODS Literature contained in PubMed and BioMed Central databases was searched using keywords such as rehabilitation, sport, musculoskeletal injuries, physical activity, pain management, exercise, therapy. Referenced sources in selected publications and thematic textbooks were also utilized. CONCLUSIONS Musculoskeletal injuries may result in significant functional limitations; however, their negative consequences can be effectively minimized through the timely initiation of structured rehabilitation. Exercises should be introduced gradually and adjusted to the injury stage to avoid excessive load on healing tissues. Adequate pain management is essential to support early mobilization and optimize recovery outcomes in athletes.